Evaluation of some chemical parameters of powder milk available in Mymensingh town (Journal of the Bangladesh Agricultural University, 2012)
The study was undertaken to evaluate some chemical parameters of powder milk available in Mymensingh town. Powder milk samples of six different brands namely Kwality, NIDO, Diploma, Anchor, Farmland & Starship were collected from local market. Powder samples were analyzed to know the chemical (PH, acidity, fat, protein, lactose, ash, moisture, solids-not-fat, total solids) characteristics. PH, acidity of all samples was almost similar to the cow milk  when the dried milk was reconstituted. PH ranged from 6.6-6.8, acidity from 0.10-0.15, fat from 26.198-27.89 g/100 g,  protein from 25.22-27.01 g/100g, lactose from 36.63-37.65 g/100g, ash from 5.34-5.48 g/100g, moisture from 3.36-4.48 g/100g, solids-not-fat from 67.99-70.07 g/100g, total solids from 95.51-96.63 g/100g, among the brands of powder milk. Statistical analysis showed significant variation for (PH and acidity) among different powder milk brands. chemical parameters in all brands of milk powder was found as per recommended standard. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12099 J. Bangladesh Agril. Univ. 10(1): 95100, 2012